If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12n + -3n = 5 + -1n Combine like terms: 12n + -3n = 9n 9n = 5 + -1n Solving 9n = 5 + -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. 9n + n = 5 + -1n + n Combine like terms: 9n + n = 10n 10n = 5 + -1n + n Combine like terms: -1n + n = 0 10n = 5 + 0 10n = 5 Divide each side by '10'. n = 0.5 Simplifying n = 0.5
| 12-3n=5-n | | x(x-3)-51=-3x+13 | | 40+x+45+45=180 | | 105=2x+7x-3 | | 30x+100=44x+0 | | 23+69-5=23 | | 2c=73 | | X(25+20x^2)=0 | | 7+2u=3 | | 18=-6y+4(y+6) | | -(-2)-1=1 | | -41=-7x+3x+7 | | X^2+4c-32=0 | | n+0.6n=64 | | 3(2x)=6x-7 | | 3(2)=6x-7 | | -16=23 | | r=4K-9S | | 4x^2+33x-8=0 | | n+5=-9 | | 12r+8=32 | | 14=2l+4w-1 | | 3*24-9+8x+12=180 | | X-8-7x-9-2x=38 | | 90=x+x+4+3x-9 | | 2x+3(1)=11 | | 4(u+6)-7u=3 | | 3x+(3x+6)=5 | | 3(4)+5y=17 | | 15t-5t^2+3t^32=0 | | 3n^2-6n+7=0 | | 3(x+4)+2x-6+5(-x-1)= |